Association of nutritional patterns and arterial hypertension in Russia: does it exist? - M. A. Lantseva; A. N. Sasunova; A. V. Vlasova; V. S. Kropochev; V. I. Pilipenko; S. V. Morozov; V. A. Isakov (Терапевтический архив, 2020)
Aim. To evaluate nutritional patterns in patient with arterial hypertension (AH) compared to the control group without elevated blood pressure.